Contact sensitization to essential oils: IVDK data of the years 2010–2019. (25th April 2022) - Geier, Johannes; Schubert, Steffen; Reich, Kristian; Skudlik, Christoph; Ballmer‐Weber, Barbara; Brehler, Randolf; Weisshaar, Elke; Uter, Wolfgang
Abstract: Background: Essential oils (EOs) are widely used in cosmetics, perfumes, massage fluids, aroma therapy and natural medicine. Some EOs contain contact sensitizers. Objectives: To describe the frequency of sensitization to EOs in dermatitis patients presenting in skin clinics including concomitant reactions, to evaluate the EO patch test preparations and to identify patient groups with an increased risk of EO sensitization. Patients and methods: Retrospective analysis of data from the Information Network of Departments of Dermatology (IVDK), 2010–2019. Results: Twelve EOs were patch tested in an aimed manner in 10 930 patients, of whom 908 (8.3%) reacted to at least 1 EO. Only 6 EOs elicited more than 1% positive patch test reactions: ylang ylang (I + II) oil (3.9%), lemongrass oil (2.6%), jasmine absolute (1.8%), sandalwood oil (1.8%), clove oil (1.6%) and neroli oil (1.1%). Concomitant reactions among EOs or to EOs and fragrances were frequent. Among EO‐positive patients, women, leg dermatitis patients, patients aged 40 years or more, masseurs and cosmeticians were over‐represented. Conclusions: Sensitization to EOs occurs, albeit infrequently in most cases. Masseurs and cosmeticians have an increased risk of sensitization to EOs. Abstract : Allergic reactions to most EOs mostly cannot be traced back to single fragrance components, are often accompanied by contact allergy to other fragrances/EOs, and occur preferably in women, patients aged 40+, leg dermatitis patients, masseurs and cosmeticians.